MODERASI CORPORATE SOSIAL RESPOSIBILITY TERHADAP PENGARUH KINERJA KEUANGAN PADA NILAI PERUSAHAAN - Bulan, A.A.Ayu Trisna; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 8 No 2 (2014), 2014)
Sustainability is not just because of the condition of profit, but also company's role in maintaining environment (triple botton line). Mining companies in Indonesia is obliged to safeguard the environment by implementing CSR . This study intends to determine the corporate social responsibility can the moderating influence of financial performance proxied by ROA on firm value proxied by PBV. This study uses secondary data including mining companies. Information disclosure is examined in this study reported a company's CSR report for 5 consecutive years. There are 38 mining companies and only 27 companies that disclose CSR report. By using regression moderation (MRA) obtained that the CSR effect on ROA relations on PBV, which means that CSR is able to moderate influence on the value of the company's financial .
Keywords: corporate social responsibility, financial performance, corporate value